Diabetes Type 2 in Neurologically Impaired Children and Adolescents Without Obesity: A New Emerging Entity? - Calcaterra, Valeria; Cena, Hellas; De Silvestri, Annalisa; Girgenti, Vincenza; Bommarito, Denisia; Pelizzo, Gloria (Frontiers in Neurology, 2019)
Background: Insulin resistance (IR) plays a key role in the pathogenesis of type 2 diabetes (T2D). In neurologically impaired (NI) children unfavorable cardio-metabolic risk profile with high prevalence of IR has been reported. We evaluated the prevalence of T2D in NI children and adolescents, in order to define if a dedicated glucose monitoring may be recommended in these subjects. Methods: We retrospectively evaluated 63 patients (11.4±4.0 years) with severe disabilities. Auxological parameters were recorded. Metabolic blood assays included fasting blood glucose (FBG), fasting insulin, triglycerides (TG). IR was detected with the homeostasis model assessment for insulin resistance (HOMA-IR>97.5th percentile for age and sex) and triglyceride-glucose index (TyG index>7.88). Elevated FBG was defined with values >100 mg/dl. T2D was defined according to American Diabetes Association criteria. Results: impaired insulin sensitivity, pathological TyG index and elevated FBG were observed respectively in 41.3%, 63.5% and 11.1% patients. T2D was diagnosed in 3.2% asymptomatic patients. The prevalence of diabetes was higher in prepubertal compared to pubertal subjects (p=0.03). Conclusions: T2D in NI children and adolescents without obesity could represent a new emerging entity. IR and/or surrogate markers of IR index may be useful for the primary screening of this at-risk disabled population so as to prevent diabetes.